Initial pyrolysis mechanism and product formation of cellulose: An Experimental and Density functional theory(DFT) study - Qing Wang (Nature Portfolio, 2020)
Abstract In this paper, analytical pyrolyzer coupled with a gas chromatography–mass spectrometry set-up (Py-GC/MS) and density functional theory(DFT) theory was used to reveal the initial pyrolysis mechanism and product formation mechanism of cellulose pyrolysis. We demonstrated an experimentally benchmarked molecular simulation approach that delineates pyrolysis process of cellulose. Experimental results indicated that the cellulose pyrolysis products mostly incorporate levoglucosan (LG), glycolaldehyde (HAA), 5-hydroxyfurfural (5-HMF), and the like. The constituents of fast pyrolysis products of cellulose and cellobiose demonstrated the identical trend, although the contents of certain products are different. Laying the foundation of experimental analysis, the reaction pathways of four categories of cellulose pyrolysis were outlined using DFT theory; the pathways are those of generating LG, HAA, and 5-HMF and the dehydration reaction in the process of cellulose pyrolysis. Also, by comparing the energy barriers of various reactions, the optimal pathway of different reactions were summarized. The deduced cellulose pyrolysis reaction pathway opened up new ideas for studying the pyrolysis behavior of cellulose.